Development of a Project-Based Learning Oriented Textile Craft Learning Module to Enhance Student Creativity - Nurhijrah, Nurhijrah; Hamsar, Israwati (Jurusan Pendidikan Teknik Elektro, 2026)
This study aimed to develop, validate, and evaluate the effectiveness of a Project-Based Learning (PjBL)-oriented Textile Craft learning module designed to enhance students’ creativity. The development adopted the 4D model (Define, Design, Develop, Disseminate), although the study was limited to the Develop phase only. The module was validated by three experts (content, media, and language) using standardized feasibility instruments. A limited trial was conducted with 10 students, followed by a main implementation involving 35 fifth-semester students from the Family Welfare Education programme, Fashion Design concentration. Creativity was assessed using pretest–posttest measures based on indicators of imagination, originality, flexibility, and elaboration. The results showed that the module achieved a “highly feasible” category with an average validation score of 91.3%. The paired sample t-test indicated a significant increase in student creativity after using the module (p < 0.05). The novelty of this research lies in the integration of explicit creativity indicators within each PjBL stage and the design of contextual project activities tailored to meet vocational learning needs. This study contributes a practical and adaptive module model for enhancing creativity in vocational education. However, the study is limited by its implementation scope, which involved only one class and did not extend to the full dissemination phase.